The effect of sketch and render quality and design experience on concept evaluation in engineering design - Detchprohm, Nisha; Schauer, Anastasia; Stokes, Haley; Fu, Katherine (Research in engineering design, 2025)
Illusory correlation (IC) is a cognitive bias that appears when decisions are based on false perception of patterns from limited data and can prevent subjects from detecting present correlations. It appears in design or psychology studies as a secondary bias, but has not been studied in-depth in engineering design. This research examines the presence of IC during concept evaluation of the engineering design process and how current engineering design education may mitigate the appearance of IC. To examine IC, different products at four different sketch quality levels and render quality levels, from quick hand drawing to shaded product render, were presented to participants through a survey-based data collection instrument. The four sketch and/or render quality levels simulate the variety of presented drawings when a design engineer is evaluating colleagues’ concepts during group work. Participants, 70 undergraduate (novice) and 21 graduate (advanced) engineering students at a major southeast US institution, were asked to rank these products based on a series of function-based and preference-based attributes. The collected data were analyzed to see if sketch and/or render quality impacted participants’ ability to gage functionality of the presented products. Results indicated no statistically significant linear correlation between better rankings of products and the sketch and/or render quality level of the provided depictions for function-based questions; however, a non-linear relationship was present for preference-based questions where participants gave higher rankings to products drawn at intermediate quality levels. No statistically significant differences were found in the strength of correlations between rankings and sketch and/or render quality levels in the comparison of novice and advanced student designers, but advanced student designers’ perception of product functionality was more strongly correlated to pre-determined baseline answers based on user ratings of the selected products. This may indicate less vulnerability to IC bias with more design engineering education due to a stronger intuition for and understanding of product functionality based on visual inspection.